Lexical Diffusion and Word Frequency in Phonological Borrowing: o/ou and ais/ois in the History of French - Holder, Maurice (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
In the lexical diffusion of sound change, and of processes involving phoneme replacement such as analogy or borrowing, word frequency is often cited as a possible factor determining which lexical items are first affected. As regards dialect borrowing, it has been noted that the most frequent items are likely to be first affected. Two cases from the history of French are examined here: in one case, replacement of ou by o borrowed from Latin, it is the least frequent words which are affected. This borrowing however falls into a different category of borrowing, namely cultural borrowing (Bloomfield, ch. 25), which by its very nature affects learnèd and literary (therefore infrequent) vocabulary first. The other case examined is a case of dialect mixture resulting in fluctuation between ais and ois and eventual lexical redistribution of the two sounds. In one category, that of geographic adjectives, the two sounds are more or less evenly distributed among lexical items (e.g. japonais/chinois), and word frequency seems to be relevant only for a few items such as anglais and français. It is open to speculation what factors may have been responsible for the present-day lexical distribution of the two adjectival suffixes, and an ad hoc explanation will be attempted.